Angels & demons [videorecording (DVD)] - Koepp, David; Goldsman, Akiva; Hanks, Tom; McGregor, Ewan, 1971-; Zorer, Ayelet; Skarsgård, Stellan; Favino, Pierfrancesco; Kaas, Nikolaj Lie, 1973-; Mueller-Stahl, Armin, 1930-; Zimmer, Hans; Brown, Dan, 1964- (Sony Pictures Home Entertainment, 2009)
Harvard symbologist Robert Langdon discovers evidence of the resurgence of the most powerful underground organization in history, the Illuminati. Upon learning of an unstoppable terrorist act against the Vatican, Langdon travels to Rome and joins forces with Italian scientist Vittoria Vetra and together they will follow the 400-year-old Path of Illumination that leads to the Vatican's only chance for survival.